la investigación escolar para potenciar habilidades científicas en el aula (2019)
In the present study, it is evident the implementation of a didactic cycle, whose purpose is to take the research to the classroom, so that the student is the protagonist of his own learning process, starting from his interests and motivation. The design and implementation of the cycle showed that a focal group of 13 students from eighth grade of the Educational Institution Antonio Derka-Santo Domingo have begun to develop scientific skills, as they are able to observe, do research, propose and argue about genetic issues, through case studies that were based on problematizing questions formulated and contextualized by the students.